IRON SILICIDE AND NATIVE SILICON INCLUSIONS IN MOISSANITE FROM THE SYTYKAN KIMBERLITE PIPE - Pankov V.Yu.; Spetsius Z.V. (My University, 1989)
The results of our detailed investigation of inclusions in moissanite from the Sytykan kimberlite pipe are given. Comparison of available information on inclusions in moissanite from different igneous rocks shows that they are uniform in composition and consist of native silicon, iron and titanium silicides, and silicon carbide. In inclusions in moissanite from kimberlite and mafic rocks, though, there are no phases significantly enriched in Mg and Ca. The geochemical specificity of the parent melt is revealed only by the trace-element content of the iron silicide. This indicates that the conditions of moissanite formation are controlled not so much by the composition of magma as by the particulars and intensity of its metamagmatic alteration by a reducing fluid.